The linkage between denitrification activity, N gas emissions, and the size of the denitrifier community in pasture soils - Čuhel, Jiří (Jihočeská univerzita, 2011)
The linkage between denitrification activity, N gas emissions, and the size of the denitrifier community in soils of an upland pasture was investigated. Special emphasis was placed on soil pH as a regulating factor, the spatial distribution of denitrification, and the degree of cattle impact. The thesis has been based on field and laboratory measurements using both conventional and modern methods of soil ecology.
The linkage between denitrification activity, N gas emissions, and the size of the denitrifier community in pasture soils
Keywords: denitrification; soil; nitrous oxide; dinitrogen; pasture; pH; emissions; denitrifier abundance; qPCR; 15N; denitrification; soil; nitrous oxide; dinitrogen; pasture; pH; emissions; denitrifier abundance; qPCR; 15N